The incidence of significant correlations between body height and weight and foot parameters among 7-13-year-old children of both sexes and environments - Mrozkowiak, Mirosław; Brzozowska, Malina; Posłuszny, Bartosz (Journal of Education, Health and Sport, 2019)
The purpose of this study was to present the incidence of significant correlations between body weight and height and the selected parameters of feet among 7-13-year-old children. Material and methods. The study which was conducted among children aged 7-13 years during the period of 3 years, in 6 half-year editions, allowed the author to record 16462 observations with regard to the measurement of 48 parameters describing feet, body weight and height. The photogrammetric method was used to measure the selected parameters. Conclusions 1. Among children aged 7-13 years, body height revealed significantly more frequent correlations with the parameters of feet than body weight. 2. Body height was reported to reveal more frequent significant correlations with the parameters of feet than body weight among boys and girls. As regards girls involved in the study, the proportions concerning the frequency of relationships concerning body height were similar to the percentage represented by boys whereas body-weight-related correlations were more frequent. Body weight and height were reported to correlate more often with the parameters of feet in the case of children living in the urban areas than those from the rural regions. 3. Among boys, the most frequent significant correlations between body weight and height and the parameters of feet were observed in subjects living in the urban environment. The percentage of relationships between body weight parameters observed in the rural environment was very low. Among girls from towns and cities, the prevalence of correlations between body weight and height outnumbered the rate of relationships in the rural environment.